2020
DOI: 10.1002/ceat.201900271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Tension on Hydrodynamics and Mass Transfer Coefficient in Airlift Reactors

Abstract: The hydrodynamics and volumetric mass transfer coefficient play important roles in the design and scale-up of airlift reactors. The effect of surface tension on hydrodynamics and volumetric mass transfer coefficient in internal loop airlift reactors was investigated. With reduction of the surface tension of the fluid, the hydrodynamic parameters raised, namely, gas phase holdup, flow regime transition point, and interfacial area, whereas the bubble diameter as well as the liquid velocity decreased and the volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Other variables related to the aeration process in bioreactors are the superficial velocity of the gas, which permits the calculation and inference of the air bubbles' behavior in the bioreactor, and the observation of their coalescence in the medium. The superficial velocity is controlled by the aeration rate [119,187] showed that plant cell cultures, when subjected to hydrodynamic stresses, can change their color and increase the PDSM production as a defense mode. Nevertheless, as mentioned above, aeration also has an effect on the mixing and mass transfer, so low aeration conditions will lead to poorly homogeneous conditions and limitations on cell growth due to the presence of sedimentation, or the development of microenvironments due to concentrations gradients.…”
Section: Aerationmentioning
confidence: 99%
“…Other variables related to the aeration process in bioreactors are the superficial velocity of the gas, which permits the calculation and inference of the air bubbles' behavior in the bioreactor, and the observation of their coalescence in the medium. The superficial velocity is controlled by the aeration rate [119,187] showed that plant cell cultures, when subjected to hydrodynamic stresses, can change their color and increase the PDSM production as a defense mode. Nevertheless, as mentioned above, aeration also has an effect on the mixing and mass transfer, so low aeration conditions will lead to poorly homogeneous conditions and limitations on cell growth due to the presence of sedimentation, or the development of microenvironments due to concentrations gradients.…”
Section: Aerationmentioning
confidence: 99%
“…The overall gas holdup was measured using the differential pressure method. Ignoring the pressure difference caused by gas density, the overall gas holdup has the following relationship with the pressure difference between the two ends of the measuring point [29]: comprehensively investigate the hydrodynamic characteristics in different flow regimes, the superficial gas velocity range was from 0.9 to 9.1 cm/s. The overall gas holdup was measured using the differential pressure method.…”
Section: Experimental Workmentioning
confidence: 99%
“…The overall gas holdup was measured using the differential pressure method. Ignoring the pressure difference caused by gas density, the overall gas holdup has the following relationship with the pressure difference between the two ends of the measuring point [29]: The overall gas holdup was measured using the differential pressure method. Ignoring the pressure difference caused by gas density, the overall gas holdup has the following relationship with the pressure difference between the two ends of the measuring point [29]:…”
Section: Experimental Workmentioning
confidence: 99%